CompTIA Security+ certification practice exams (Exam SY0-401) - Lachance, Daniel (McGraw-Hill Education, 2014)
This edition (Exam SY0-401) is filled with more than 800 realistic practice questions--including new performance-based questions--to prepare for this exam. In-depth explanations of both the correct and incorrect answers are included for every question. This practical guide covers all official objectives for Exam SY0-401 and is the perfect companion to CompTIA Security+ Certification Study Guide, second edition. Topics include: networking basics and terminology; security terminology; security policies and standards; types of attacks; system security threats; mitigating security threats; implementing system security; securing the network infrastructure; wireless networking and security; authentication; access control; cryptography; managing a public key infrastructure; physical security; risk analysis; disaster recovery and business continuity; computer forensics; security assessments and audits; monitoring and auditing. --
Print version record
Keywords: Electronic data processing personnel -- Certification; Computer security -- Study guides -- Examinations; Computer networks -- Study guides -- Security measures -- Examinations; Sécurité informatique; Examens; Guides de l'étudiant; Réseaux d'ordinateurs; Sécurité; Mesures; Examens; Guides de l'étudiant; Computer networks; Security measures; Examinations; Computer security; Examinations; Electronic data processing personnel; Certification; examination study guides; Study guides; Guides de l'étudiant